Dialectics of Service Quality and Spirituality in Islamic Early Childhood Education - A Wathon; Mujamil Qomar; Nur Efendi (AS-SABIQUN, 2026)
This study is motivated by the limited integration of service quality frameworks and spirituality in Islamic early childhood education, despite their significant role in supporting holistic child development. This study aims to analyze the dialectical relationship between service quality and spirituality based on recent literature published between 2024 and 2025. A qualitative design using a systematic literature review approach was employed. Data were collected from 35 indexed journal articles published during 2024–2025 and analyzed using thematic analysis. The findings reveal that service quality frameworks are increasingly integrated with Islamic ethical principles, such as amanah and ihsan, while leadership and teacher professionalism function as key mediating factors. In addition, workplace spirituality contributes indirectly to service quality through job satisfaction and organizational commitment. However, challenges remain in policy alignment, teacher training, and technological integration. The study concludes that an integrative model combining spiritual values and quality assurance mechanisms is essential for achieving holistic educational outcomes in Islamic early childhood education. This study contributes to the theoretical development of Islamic education quality models and offers practical recommendations for policymakers and educators to strengthen spiritually grounded quality assurance systems.